CAPITALISING ON TRANSLATION MARKET DATA IN THE FIELD OF COMMERCIAL LAW - WIĘCŁAWSKA, Edyta (Comparative Legilinguistics, 2019)
The author presents data gathered in an online survey questionnaire (https://www.interankiety.pl/i/RGmj5rDv) which is a part of a broader research project related to the quality of translation of English language documents in the field of commercial law that are processed in the judicial registration proceedings in reference to the entities subject to registration at the Register of Entrepreneurs of the National Court Register (RP, KRS). The questions and hypotheses posed by the author relate to the relationship or comparison of nation-wide data concerning cases with foreign element in the context of the documents in translation on file in the National Court Register (source texts and their certified translations). The survey is the first stage of this project and has been ascribed a number of aims: allowing for a definition of the genre profile of the corpus texts; identifying the general sociologically conditioned tendencies in their structure; and – primarily – determining the practically feasible search criterion for compiling a design corpus for further quantitative and qualitative analysis of selected language structures (the ensuing stages of the said project).